(Benzyl isocyanide)gold(I) pyrimidine‐2‐thiolate complex: Synthesis and biological activity. (11th January 2018) - Fereidoonnezhad, Masood; Shahsavari, Hamid R.; Lotfi, Elaheh; Babaghasabha, Mojgan; Fakhri, Motahareh; Faghih, Zeinab; Faghih, Zahra; Hassan Beyzavi, M.
Abstract : The reaction of [(Me2 S)AuCl] with an equimolar amount of benzyl isocyanide (PhCH2 NC) ligand led to the formation of complex [(PhCH2 NC)AuCl] (1 ). The solid‐state structure of1 was determined using the X‐ray diffraction method. Through a salt metathesis reaction, the chloride ligand in1 was replaced by pyrimidine‐2‐thiolate (SpyN − ) to afford the complex [(PhCH2 NC)Au(η 1 ‐S‐Spy)] (2 ), which was characterized spectroscopically. The cytotoxic activities of1 and2 were evaluated against three human cancer cell lines: ovarian carcinoma (SKOV3), lung carcinoma (A549) and breast carcinoma (MCF‐7). Complex2 showed higher cytotoxicity than cisplatin against SKOV3 and MCF‐7 cancer cell lines. It showed a strong anti‐proliferative activity with IC50 of 7.80, 6.26 and 6.14 μM, compared with that measured for cisplatin which was 7.62, 12.36 and 11.47 μM, against A549, SKOV3 and MCF‐7 cell lines, respectively. The induction of cellular apoptosis by2 was also studied on MCF‐7 cell line. Our results indicated that2 could induce apoptosis in cancerous cells in a dose‐dependent manner. Abstract : Gold(I) complexes with isocyanide and thiolate ligands were prepared and studied for in vitro cytotoxic activity against three human cancer cell lines: ovarian carcinoma (SKOV3), lung carcinoma (A549) and breast carcinoma (MCF‐7). Complexes1 and2 were also investigated for their apoptosis effect. Complex2 exhibited higher cytotoxicity than cisplatin.